MOLECULAR IMAGING AND INTRAOPERATIVE RADIONAVIGATION IN PROSTATE CANCER - P. O. Rumyantsev (Sibirskij Onkologičeskij Žurnal, 2021)
Introduction. Prostate cancer is one of the most common malignant neoplasms. Strategies to improve early diagnosis and subsequent therapy are being improved. An emphasis is placed on maintaining the quality of life and working capacity of patients after treatment. This can be achieved by improving methods of focal therapy, which depends on the accuracy of topical diagnosis and classification of the tumor. Hybrid molecular imaging (pet/ct and spect/ct) is used in addition to the methods of structural imaging (ultrasound, ct, mri). Intraoperative imaging using radionavigation systems is also used in open and endoscopic surgery for prostate cancer. Currently, it is a tool capable of reducing the invasiveness of surgery, localizing the area of metastatic lesions with a sensitivity and specificity of up to 95 %.Objective of the study: an overview of current and promising future methods of intraoperative radio navigation in the surgical treatment of prostate cancer.Material and methods. The review presents the methods of intraoperative radionavigation in the surgical treatment of prostate cancer. Radionavigation in the context of using tumarotropic radiopharmaceutical based on a prostate-specific membrane antigen, in which the drug accumulates in all tumor foci expressing this receptor, is also considered.Conclusion. The use of preoperative hybrid imaging and radio-guided surgery facilitate lesion identification and resection. Gamma probing allows detection of psma-positive tumor foci regardless of their depth. Fluorescence imaging methods (icg, photodynamic diagnostics, autofluorescence) are also used for intraoperative detection of pathological foci in real time. Multichannel gamma probing and cherenkov radiation detection, which combine the advantages of indirect and direct intraoperative imaging, have enormous potential.